INTEGRATING INFORMATION LITERACY INTO ISLAMIC BOARDING SCHOOL CURRICULUM: A STUDY AT IBADURRAHMAN PESANTREN AT STABAT - Wahyu Ramadhan; Yusnaili Budianti; Mohammad Al farabi (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2025)
Islamic boarding schools (pesantren) in Indonesia are undergoing significant transformation as they face increasing demands to integrate traditional Islamic scholarship with modern educational competencies. This study examines curriculum dynamics at Ibadurrahman Islamic Boarding School in Stabat, Langkat Regency, with a particular focus on the integration of information literacy as a foundational competency for students in a digital era. Using a qualitative descriptive design, data were collected through semi-structured interviews with key academic stakeholders-including the principal, deputy head of curriculum, and teaching staff-and supported by document analysis of syllabi, instructional materials, and institutional policy documents. The findings reveal that Ibadurrahman Pesantren adopts a dual-track curriculum combining national general-education standards with classical Islamic studies, enabling students to master both religious knowledge and modern scientific skills. Information literacy emerges not merely as a technical ability, but as an ethical and epistemic practice embedded in Islamic values, where students are trained to access, evaluate, and apply information responsibly across religious and academic contexts. This integration supports holistic development, fostering spiritual character, cognitive skills, digital competence, and academic readiness for higher education and professional paths. The study highlights the role of institutional leadership, pedagogical innovation, and continuous adaptation to national curriculum reforms in sustaining curriculum relevance. Overall, the results demonstrate that information literacy, when grounded in Islamic ethical principles, can serve as a strategic bridge between tradition and modernity, positioning pesantren as progressive learning institutions capable of developing morally grounded and information-literate Muslim youth equipped for contemporary global challenges.